Implementation of Internasional-Based Curriculum Alfa and Friends to Development Early Childhood Language - Amalia, Ika Nurul; Fidrayani, Fidrayani (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Early childhood education plays a vital role in language development, which is essential for children’s overall growth and future success. This research aims to describe the implementation of an international curriculum to support language development. Using a qualitative approach, data were collected through interviews with the teacher and a class teacher, observations involving 17 children, and document analysis including lesson plans and student assignments. Thematic analysis was conducted to fully interpret the data collected. The results show the curriculum stimulates language development in children. The study highlights the importance of innovative and interactive methods, these findings have important implications for curriculum design, encouraging the adoption of similar approaches to improve children's early language acquisition and holistic development.